Ascorbic acid toxicity is related to oxidative stress and enhanced by high light and knockdown of chloroplast ascorbate peroxidases in rice plants - Castro, Jamyla L. S.; Lima-Melo, Yugo; Carvalho, Fabricio E. L.; Feitosa, Antonio G. S.; Lima Neto, Milton C. [UNESP]; Caverzan, Andréia; Margis-Pinheiro, Marcia; Silveira, Joaquim A. G. (Springer Nature, 2018)
Toxicity caused by high concentrations of ascorbic acid (AA) has been widely reported in animal cells but is scarcely described in plants. In this study, rice plants deficient (knockdown) in two chloroplast ascorbate peroxidases (APX7/8) and non-transformed (NT) were exposed to wide exogenous AA concentrations in the presence of low light and high light (HL). Reduced (ASC) and oxidized (DHA) ascorbate reached much higher concentrations in symplast compared to the apoplastic space, and high redox states were found in both cellular compartments. Exogenous AA concentrations above 30 mM caused strong cellular and oxidative damage indicated by decreased cell integrity and increased lipid peroxidation in leaves. These toxic effects were strongly enhanced by HL and, to a small extent, by deficiency of both chloroplastic proteins APX7/8. The combination of HL and high AA concentration induced a strong increase in H2O2, associated with decrease in the content of chlorophylls and carotenoids. High AA concentrations strongly induced stomatal closure and impairment in CO2 assimilation, in combination with decreased quantum efficiency of photosystem II (PSII) and PSI. We postulate that oxidative stress caused by AA toxicity in the presence of HL was induced by over-production of reactive oxygen species due to an imbalance between excess energy in the photosystems and low CO2 assimilation, which was related closely to strong decrease in stomatal conductance. In addition, high ASC levels might have acted as a pro-oxidant in the presence of high H2O2 concentrations, stimulating the Fenton reaction and contributing to the intensification of oxidative stress in rice leaves.
Keywords: Ascorbic acid; Oryza sativa; Oxidative stress; Photo-oxidative stress; Photosynthesis; Reactive oxygen species